PENGEMBANGAN MEDIA PEMBELAJARAN KOLEKSI AWETAN CANGKANG GASTROPODA UNTUK KELAS X SMA - Rauda Syafitri; Afreni Hamidah (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2016)
ABSTRACT The purpose of this research is to develop a product that form of a collection gastropods shell preserved that can be used as a learning media both theoretical and practical work at class x senior high school. The product is a collection of learning media preserved shell of gastropod which has three parts, namely the wardrobe collection, collection boxes and shelves collection. This type of research is ADDIE development model. The results showed the revised product media experts, subject matter experts and trial of respondents is as follows. Media validation is performed three times.Â At the first validation obtained a percentage of 50.7% and categorized not good. The second validation obtained percentage of 65.3% and is average, and the third validation obtained a percentage of 76% categorized as good and media can be used to trial. Then, validation matter is done four times. At the first validation obtained a percentage of 29.3% and classified is not very good. At the second validation obtained a percentage of 65.3% and is average. At the third validation obtained a percentage of 82.7% and good categorized. At the fourth validation obtained by percentage of 88% categorized as very good. After validated and revisions, the product tested on small groups and obtained the students' response was 91% with a very good category. Learning media of collection gastropods shell preserved feasible for use in the learning process. Â Key word: Â media learning , a collection of gastropod shells preserved development